2023
DOI: 10.3390/jcm12103497
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib for Mood Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Adam Gędek,
Zofia Szular,
Anna Z. Antosik
et al.

Abstract: The effects of celecoxib on a broad spectrum of mood disorders and on inflammatory parameters have not yet been comprehensively evaluated. The aim of this study was to systematically summarize the available knowledge on this topic. Data from both preclinical and clinical studies were analyzed, considering the efficacy and safety of celecoxib in the treatment of mood disorders, as well as the correlation of inflammatory parameters with the effect of celecoxib treatment. Forty-four studies were included. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 115 publications
0
7
0
2
Order By: Relevance
“…To date, no study has been conducted to assess the efficacy of anti-inflammatory treatment in ADHD, with used e.g., non-steroidal anti-inflammatory drugs (NSAIDs). Clinical trials have confirmed the efficacy and safety of NSAIDs in other mental disorders in which inflammation plays a role in the pathogenesis, such as mood disorders ( 42 , 43 ). However, there are studies evaluating additional treatment of nutraceuticals with postulated anti-inflammatory properties in ADHD.…”
Section: Discussionmentioning
confidence: 97%
“…To date, no study has been conducted to assess the efficacy of anti-inflammatory treatment in ADHD, with used e.g., non-steroidal anti-inflammatory drugs (NSAIDs). Clinical trials have confirmed the efficacy and safety of NSAIDs in other mental disorders in which inflammation plays a role in the pathogenesis, such as mood disorders ( 42 , 43 ). However, there are studies evaluating additional treatment of nutraceuticals with postulated anti-inflammatory properties in ADHD.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, recent systematic reviews have also concluded that celecoxib may have a beneficial effect on MDD in humans [ 250 , 251 ]. A systematic review based on 44 studies found that a dose of 400 mg/day used for 6 weeks is effective as a complementary treatment for MDD [ 251 ].…”
Section: Antidepressant Effects Of Anti-inflammatory Drugsmentioning
confidence: 99%
“…Of note, recent systematic reviews have also concluded that celecoxib may have a beneficial effect on MDD in humans [ 250 , 251 ]. A systematic review based on 44 studies found that a dose of 400 mg/day used for 6 weeks is effective as a complementary treatment for MDD [ 251 ]. Although these results are promising, clinical studies have not yet been able to associate the antidepressant effects of celecoxib with the attenuation of inflammatory mediators.…”
Section: Antidepressant Effects Of Anti-inflammatory Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its role in depressive neuroprogression generally, immune-metabolic dysregulation is also increasingly implicated in a subset of treatment-refractory forms of depressive illness [ 1 , 8 , 9 ]. In that vein, several randomized control trials (RCTs) have established preliminary support for adjunctive anti-inflammatory treatment in treatment-resistant depression [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In a recent double-blind, placebo-controlled RCT in treatment-resistant bipolar depression (TRBDD), we demonstrated that clinical remission can be induced with adjunctive immune modulatory treatment with the selective cyclo-oxygenase 2 (COX2) inhibitor, celecoxib (CBX), in conjunction with an adequately dosed selective serotonin reuptake inhibitor (SSRI), escitalopram (ESC) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%